Formulation and Characterization of Clotrimazole Micro Emulsion for Topical Drug Delivery - Vamakshi Thaker; A.K. Singhai; Dilip Kumar Tiwari (Indian Journal of Pharmacy & Drug Studies, 2023)
An antimycotic drug like clotrimazole is used for treating Candida albicans and other fungal infections. Clotrimazole seemsto be a topical therapy treating vulvovaginal candidiasis, tineapedis, and oropharyngeal candidiasis. That is a synthetic azoleantimycotic. By decreasing the production of ergosterol, this drug inhibits fungal growth. Clotrimazole has become amedication of interest for a variety of illnesses, including sickle cell anemia, malaria, and some cancers, in addition to itsantimycotic properties. It is mixed with other molecules to create clotrimazole compounds with enhanced pharmacologicaleffectiveness. Numerous novel pharmaceutical formulations enabling variable releases developed. Clotrimazole is a welltolerated,little-adverse drug. However, certain immunocompromised individuals are developing treatment resistance. In thisstudy, we discussed the pharmaceutical chemistry, use, and pharmacology of clotrimazole.